2015
DOI: 10.1007/s00122-015-2526-9
|View full text |Cite
|
Sign up to set email alerts
|

Fine-mapping and validating qHTSF4.1 to increase spikelet fertility under heat stress at flowering in rice

Abstract: This study fine mapped and validated a QTL on rice chromosome 4 that increases spikelet fertility under high temperature (over 37 °C) at the flowering stage. Climate change has a negative effect on crop production and food security. Understanding the genetic mechanism of heat tolerance and developing heat-tolerant varieties is essential to cope with future global warming. Previously, we reported on a QTL (qHTSF4.1) from an IR64/N22 population responsible for rice spikelet fertility under high-temperature stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
54
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(60 citation statements)
references
References 37 publications
5
54
1
Order By: Relevance
“…From the above studies and our own evaluation, it can be concluded that high‐temperature is a major factor in regulating the stability of hybrid rice production, with hybrid rice being more sensitive to increasing temperature than indica and japonica inbreds. These findings, therefore, highlight the urgent need to address the damage caused by HDT on hybrids and develop heat‐tolerant hybrids by utilizing the genetic advances made using inbreds and landraces (Ye et al, ). In Experiment 2, HDT and HNDT significantly decreased spikelet fertility in all tested genotypes, whereas HNT moderately decreased spikelet fertility in only three hybrids (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…From the above studies and our own evaluation, it can be concluded that high‐temperature is a major factor in regulating the stability of hybrid rice production, with hybrid rice being more sensitive to increasing temperature than indica and japonica inbreds. These findings, therefore, highlight the urgent need to address the damage caused by HDT on hybrids and develop heat‐tolerant hybrids by utilizing the genetic advances made using inbreds and landraces (Ye et al, ). In Experiment 2, HDT and HNDT significantly decreased spikelet fertility in all tested genotypes, whereas HNT moderately decreased spikelet fertility in only three hybrids (Table ).…”
Section: Discussionmentioning
confidence: 99%
“…However, little is known on how the hybrid rice seed production system responds to high temperature. A number of studies have identified QTLs for heat tolerance at the flowering stage of rice, but genetically how parent plants of hybrid rice adapt to heat stress is lacking (Cao et al, 2003; Xiao et al, 2011; Ye et al, 2012, 2015). …”
Section: Introductionmentioning
confidence: 99%
“…(15.1 ± 6.3%), while, in BC 5 F 2 , spikelet fertility of plants with qHTSF4.1 (44.6 ± 13.1%) was significantly higher than in plants without the QTL (27.1 ± 9.6%) and recurrent parent IR64 (19.4 ± 8.4%) (Ye et al, 2015b). n22 has many undesirable agronomic characteristics (Manigbas et al, 2014), but the results imply the importance of making best use of the landrace as a genetic resource for future breeding challenges.…”
Section: Genetic Analyses For Emf Traitmentioning
confidence: 90%
“…To fine map and validate the effect of heat tolerance QTL qHTSF4.1, PCR-based SnP markers were developed and used to genotype BC 2 F 2 , BC 3 F 2 , BC 3 F 3 , and BC 5 F 2 populations from the cross combination of IR64/n22. The QTL interval was narrowed down to about 1.2 Mb (Ye et al, 2015b). A near-isogenic line (nIL) carrying qHTSF4.1 in the IR64 background was developed.…”
Section: Genetic Analyses For Hiss At Floweringmentioning
confidence: 99%
See 1 more Smart Citation